2022
DOI: 10.1080/07853890.2022.2146744
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and mutation spectrum in 33 Chinese families with familial exudative vitreoretinopathy

Abstract: Objective To explore the clinical manifestations and search for the variants of six related genes ( LRP5 , FZD4 , TSPAN12 , NDP , KIF11 and ZNF408 ) in Chinese patients with familial exudative vitreoretinopathy (FEVR), and investigate the correlation between the genetic variants and the clinical characteristics. Patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…1,3 Most forms of FEVR affect only the eye and may be caused by mutations in LRP5 or in about 14 other genes including FZD4, TSPAN12, NDP, and KIF11. 4 Incomplete loss-of-function mutations in LRP5 can result in a distinct form of FEVR whose phenotype includes osteoporosis and predisposition to fracture in addition to the incomplete or anomalous vascularization of the peripheral retina for which the condition is known. [4][5][6] Because OPPG and LRP5-mutation-induced FEVR arise secondary to similar genetic mechanisms, it has been proposed that the conditions are in fact a continuum and should not be considered separate entities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 Most forms of FEVR affect only the eye and may be caused by mutations in LRP5 or in about 14 other genes including FZD4, TSPAN12, NDP, and KIF11. 4 Incomplete loss-of-function mutations in LRP5 can result in a distinct form of FEVR whose phenotype includes osteoporosis and predisposition to fracture in addition to the incomplete or anomalous vascularization of the peripheral retina for which the condition is known. [4][5][6] Because OPPG and LRP5-mutation-induced FEVR arise secondary to similar genetic mechanisms, it has been proposed that the conditions are in fact a continuum and should not be considered separate entities.…”
Section: Discussionmentioning
confidence: 99%
“…4 Incomplete loss-of-function mutations in LRP5 can result in a distinct form of FEVR whose phenotype includes osteoporosis and predisposition to fracture in addition to the incomplete or anomalous vascularization of the peripheral retina for which the condition is known. [4][5][6] Because OPPG and LRP5-mutation-induced FEVR arise secondary to similar genetic mechanisms, it has been proposed that the conditions are in fact a continuum and should not be considered separate entities. 5,7,8 While the skeletal characteristics of adolescents with OPPG have been described, 9,10 the skeletal phenotypes of patients with LRP5-mutation-induced FEVR have not been explored in depth.…”
Section: Discussionmentioning
confidence: 99%
“…Related to OPPG is LRP5 variant-induced familial exudative vitreoretinopathy (FEVR; OMIM 133780 [40]), a disorder characterized by disorganized retinal blood vessel development leading to incomplete vascularization of the peripheral retina [41,42]. Clinically, FEVR displays genetic heterogeneity, and variants of at least 14 genes have been implicated in its pathogenesis [43]. These include variants in genes related to the WNT signaling pathway, e.g., LRP5, FZD4 (OMIM 604579 [44]), and CTNNB1 (OMIM 617572 [45]), which have been reported to be responsible for FEVR.…”
Section: Low Bone Mass Phenotypes Related To Lrp5mentioning
confidence: 99%
“…A more recent study by Mao et al also found lower VD of the DCP in the digenic inheritance of FEVR patients. Patients with LRP5 variants had lower foveal VD in SCP and DCP and a higher acirculatory index than TSPAN12 variants [ 75 ]. This finding shows the application of OCTA in different phenotypes and genotypes in the FEVR disease spectrum.…”
Section: Oct and Octa In Retinal Vascular Diseasesmentioning
confidence: 99%